O coordenador pedagógico como articulador das práticas avaliativas na unidade escolar: uma reflexão sobre a Avaliação da Aprendizagem em Processo (AAP) - Castro, Lilia Alves da Silva (2016)
The present research aims to investigate how the pedagogical coordinator articulates the Learning Evaluation in Process (LEP) in Pedagogical Collective Class Work (PCCW) to set it as a diagnostic test and also a the specific objectives are, identify the view that teachers have on the LEP, check if teachers heed the guidance of the pedagogical coordination for the implementation of the LEP and finally identify how teachers consider what should be the role of the principal of the teacher's stance that does not support the guidance of managers. The LEP has sent by the São Paulo State Education (SE) and aims to diagnose the learning level of students enrolled in state schools. The test has applied at the end of the three bimesters periods and aims through the extracted contents, produce guidance to educators in order to develop programs and projects that work in the students' difficulties. During the training meetings that preceded the application of this evaluation, I have observed several reactions that demonstrated aversion as the organization of time and space and the apparent indifference of students towards to the test. This work was developed in order to clarify issues that permeate the evaluation, the application and also the critical position of teachers against the LEP. To support this research we have used the technique of critical incidents, in the form describing situations. Three incidents were applied to teachers of a public school on the outskirts of a town in the metropolitan region of São Paulo. These incidents described situations on the implementation of the LEP that teachers have known and / or have experienced. The theoretical framework used to evaluation of learning was disseminated by authors such as Philippe Perrenoud, Charles Hadji, Miguel Ángel Santos Guerra, Cipriano C. Luckesi, Celso S. of Vasconcellos and Julia Falivene Alves. Regarding the research I have used the technique of critical incidents from John C. Flanagan, Laurinda Ramalho de Almeida inspired by Maria Teresa Estrela and Albano Estrela